Dietary copper triggers onset of fulminant hepatitis in the Long-Evans cinnamon rat model - Siaj, Ramsi (Baishideng Publishing Group Co., Limited, 2012)
AIM: To investigate the impact of dietary copper given at different time points on the onset of fulminant hepatitis. METHODS: The Long-Evans cinnamon (LEC) rat model of Wilson’s disease (WD) was used to study the impact of high dietary copper (hCu) on the induction of fulminant hepatitis at early or late time points of life. High Cu diet was started in rat pups or in adults (month 5) for three months. Animals that received reduced dietary copper (rCu) throughout their lifetime served as a control. Hepatitis-associated serum markers (alanine aminotransferase, aspartate transaminase, bilirubin) were analyzed in animal groups receiving hCu or rCu. Liver copper content and liver histology were revealed at sacrifice. A set of 5 marker genes previously found to be affected in injured liver and which are related to angiogenesis (Vegfa), fat metabolism (Srebf1), extracellular matrix (Timp1), oxidative stress (Hmox1), and the cell cycle (Cdkn1a) were analyzed by real-time polymerase chain reaction. RESULTS: Regardless of the time point when hCu was started, LEC rats (35/36) developed fulminant hepatitis and died. Animals receiving rCu (36/36) remained healthy, did not develop hepatitis, and survived long term without symptoms of overt disease, although liver copper accumulated in adult animals (477 ± 75 μg/g). With regard to start of hCu, onset of fulminant hepatitis was significantly (P < 0.001) earlier in adults (35 ± 9 d) that showed pre-accumulation of liver copper as compared to the pup group (77 ± 15 d). Hepatitis-associated serum markers, liver copper and liver histology, as well as gene expression, were affected in LEC rats receiving hCu. However, except for early and rapid onset of hepatitis, biochemical and molecular markers were similar at the early and late time points of disease. CONCLUSION: Rapid onset of fulminant hepatitis in asymptomatic LEC rats with elevated liver copper suggests that there is a critical threshold of liver copper which is important to trigger the course of WD.